2012
DOI: 10.2147/ijgm.s27203
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary valve balloon valvuloplasty compared across three age groups of children

Abstract: The aim of this study was to investigate the characteristics and outcomes of treating pulmonary stenosis with percutaneous valvuloplasty, and to compare them among three childhood age groups. All children under 15 years of age who had undergone pulmonary valve balloon valvuloplasty in Madani Heart Center from 2005–2009 were enrolled in this study. Data were analyzed using IBM SPSS software (SPSS, Inc, Chicago, IL). Mean (± standard deviation) age of patients was 55.5 ± 47.4 months. Two-thirds of the subjects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…9 Ghaffari group also used age categorisation in their study. 10 In our study, the smallest baby was 2.4 kg, while the maximum body weight was 40.7 kg, with a mean of 10.1 ± 8.9 kg. These results are comparable to those of Behjati et al, who reported a mean weight of 12.2 ± 4.7 kg (age ranged from 0.4 to 8 years).…”
Section: Age Categorisationmentioning
confidence: 45%
“…9 Ghaffari group also used age categorisation in their study. 10 In our study, the smallest baby was 2.4 kg, while the maximum body weight was 40.7 kg, with a mean of 10.1 ± 8.9 kg. These results are comparable to those of Behjati et al, who reported a mean weight of 12.2 ± 4.7 kg (age ranged from 0.4 to 8 years).…”
Section: Age Categorisationmentioning
confidence: 45%
“…Stanger P et al 9 in VACA registry of 26 institutions reported only 0.35 % major complications rate while 0.24 % death rate from total 822 cases of balloon pulmonary valvuloplasty. There has been a high incidence of complications of the procedure in neonates, infants and children 15,16 while most of the studies describe no major complications of BPV in children, adolescents or adult population. 17,18,3 Similarly Ezhumalai B et al 19 in his study in India reported 12% complications including major (3.7%) and minor complication (8.3%).…”
Section: Discussionmentioning
confidence: 99%